Impact of SARS-CoV-2 on the clinical outcomes and placental pathology of pregnant women and their infants: A systematic review. Issue 3 (March 2021) - Oltean, Irina; Tran, Jason; Lawrence, Sarah; Ruschkowski, Brittany Ann; Zeng, Na; Bardwell, Cameron; Nasr, Youssef; de Nanassy, Joseph; El Demellawy, Dina
Abstract: Pregnant women are susceptible to viral infections due to physiological changes such as cell-mediated immunity. No severe adverse pregnancy or neonatal outcomes have been consistently reported in 2019 novel coronavirus disease (COVID-19) positive pregnancy cases. There are controversies around the role of COVID-19 in pregnancy. A systematic review was conducted to examine clinical maternal and neonatal clinical outcomes. Studies were included if they reported SARS-CoV-2 infection among pregnant women and/or COVID-19 positive neonates as validated by positive antibody testing or viral testing using polymerase chain reaction. Case series, case reports, case-control studies, and comparative studies were included. Eight hundred and thirty-seven records were identified, resulting in 525 records for level I screening. Forty-one were included after full-text review. Results suggest elevated rates of intensive care unit (ICU) admission, gestational diabetes, preeclampsia, C-sections, pre-term birth, and C-reactive protein (CRP) in comparison to pregnant women without SARS-CoV-2. Careful monitoring of pregnancies with SARS-CoV-2 is recommended. Abstract : SARS-CoV-2; COVID-19; Pregnant women; Placental pathology; Neonates; Placenta diseases.